2018
DOI: 10.22159/ajpcr.2018.v11i6.24800
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperlipidemic Activity of Commiphora Mukul Against Atherogenic Diet-Induced Hyperlipidemia in Experimental Rats

Abstract: Objective: The aim of the present study was to investigate the effect of antihyperlipidemic activity of ethyl acetate extract of Commiphora mukul (EECM) gum resin and compares its efficacy with that of atorvastatin against atherogenic diet-induced hyperlipidemia model using rat as an experimental animal.Methods: Wistar albino rats were divided into five groups. Control animals received normal diet, hyperlipidemic control; rats treated with EECM 100 and 200 mg/kg and positive control, receiving standard drug at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Findings in our study showed significant (p<0.05) increase in serum TG, TC, LDL and VLDL and significant (p<0.05) decrease in HDL group when compared with standard pellet fed rats. Findings in our study are Similar to those of previous reports, which confirms the induction of hyperlipidemia [15][16][17][18][19].…”
Section: (A = Effect Of Test Formulation On Triglyceride B = Effecsupporting
confidence: 93%
See 2 more Smart Citations
“…Findings in our study showed significant (p<0.05) increase in serum TG, TC, LDL and VLDL and significant (p<0.05) decrease in HDL group when compared with standard pellet fed rats. Findings in our study are Similar to those of previous reports, which confirms the induction of hyperlipidemia [15][16][17][18][19].…”
Section: (A = Effect Of Test Formulation On Triglyceride B = Effecsupporting
confidence: 93%
“…Treatment with test formulation (Arogyavardhini and zpter) and standard treatment (Atorvastatin) significantly (p<0.05) elevates the decrease level of HDL in hyperlipedimic rats. The finding of our study represents similarities with the previous outcome [15].…”
Section: (A = Effect Of Test Formulation On Triglyceride B = Effecsupporting
confidence: 91%
See 1 more Smart Citation
“…This lipid-lowering activity may be due to the inhibition of hepatic cholesterogenesis and catabolic conversion of cholesterol to bile acids in the liver [51] . Randomiz Conrolled Study [52] 35…”
Section: E-and Z-guggulsterone Isomers Of the Guggalmentioning
confidence: 99%
“…Some herbal products can be used to control hyperlipidemia. Ethyl acetate extract from Commiphora Mukul can reduce TG, total cholesterol (TC), and LDL-C and increase HDL-C in the treatment of hyperlipidemia and other related disorders such as atherosclerosis (Shaik and Khan, 2018).…”
Section: Introductionmentioning
confidence: 99%